Komunikasi Antara Pelatih dengan Pemain dalam Membangun Prestasi Tim Olahraga - Bryan, Arron; Loisa, Riris (Kiwari, 2024)
This research examines the role of interpersonal communication in sports team dynamics, with a focus on the relationship between coaches and players. In the context of sports teams, interpersonal communication plays a key role in forming healthy relationships, strengthening collaboration, and improving performance. This research includes observations of how interpersonal communication influences players' motivation, self-confidence, and involvement in training and matches. Through a qualitative approach, this research explores players' experiences in receiving and giving feedback, verbal and non-verbal communication, as well as how coaches build effective interpersonal relationships. Research findings show that positive, open, and supportive communication from coaches has a significant impact on player motivation and self-confidence. In addition, it was found that coaches who apply an adaptive communication style, are sensitive to individual needs, and are able to manage conflict constructively can create a cooperative and motivating team environment. The results of this research show that openness, empathy, supportive attitudes, positive attitudes, will create equality between coaches and players. Here it means building good interpersonal communication between the two parties. If this continues to be built, good and mutually beneficial relationships will be established. Penelitian ini membahas peran komunikasi interpersonal dalam dinamika tim olahraga, dengan fokus pada hubungan antara pelatih dan pemain. Dalam konteks tim olahraga, komunikasi interpersonal memainkan peran kunci dalam membentuk hubungan yang sehat, memperkuat kolaborasi, dan meningkatkan kinerja. Penelitian ini mencakup pengamatan terhadap bagaimana komunikasi interpersonal memengaruhi motivasi, kepercayaan diri, dan keterlibatan pemain dalam latihan dan pertandingan. Melalui pendekatan kualitatif, penelitian ini menggali pengalaman pemain dalam menerima dan memberikan umpan balik, komunikasi verbal dan non-verbal, serta cara pelatih membangun hubungan interpersonal yang efektif. Temuan penelitian menunjukkan bahwa komunikasi yang positif, terbuka, dan mendukung dari pelatih memiliki dampak signifikan terhadap motivasi dan kepercayaan diri pemain. Selain itu, ditemukan bahwa pelatih yang menerapkan gaya komunikasi yang adaptif, sensitif terhadap kebutuhan individu, dan mampu mengelola konflik dengan konstruktif dapat menciptakan lingkungan tim yang kooperatif dan memotivasi. Hasil penelitian ini menunjukkan bahwa keterbukaan, empati, sikap mendukung, sikap positif, akan mewujud kesetaraan antara pelatih dan pemain. Di sini artinya terbangun komunikasi interpersonal yang baik antara kedua bekah pihak. Jika ini terus dibangun maka maka akan terjalin hubungan yang baik dan saling menguntungkan.